Effect of nanofillers with different energy levels on the electrical properties of epoxy‐based nanocomposites - Guo, Ning; Chen, Cailing; Zhang, Guangwei; Sun, Rongsheng; Wang, Yulong; Gao, Junguo (High voltage, 2024)
The authors investigate the effects of nanofillers with varying band‐gap energies on the space charge properties, breakdown field strength, and bulk resistivity of epoxy (EP)‐based composites. Additionally, the molecular orbital distribution of both the epoxy resin and nanofillers were examined through density functional theory. Experimental results indicate that the space charge accumulation within silicon dioxide/EP and germanium oxide/EP is reduced, leading to a more uniformly distributed electric field intensity within the specimen when compared to epoxy. As a result, both materials exhibit improved AC breakdown field strength and volume resistivity. Conversely, the amount of charge accumulated within tin dioxide/EP is higher, resulting in lower breakdown field strength than epoxy. The lowest unoccupied molecular orbital and the highest occupied molecular orbital energy level differences between epoxy and nanofillers introduce electron traps and hole traps at the interface, forming interfacial traps that affect the space charge distribution within the specimen, as well as the trap energy levels within the material. From the experimental results, shallow traps promote space charge accumulation and reduce the breakdown field strength, while deep traps have the opposite effect.